Multispectral satellite images to support the CIM (City Information Modeling) implementation (GEOmedia, 2022)
This work shows the processing of additional information using high and medium-resolution multispectral satelliteimages. The new information obtained from specific spectral indices will converge with the data obtained fromofficial sources in a single database, thus constituting a real parametric model of the city under study. An extended modelof urban planning called “CIM” (City Information Modeling) will be developed, to which it is possible to associateinformation of different nature, which helps to monitor and manage the city.